Detection of Majorana Bound States by Sign Change of the Tunnel Magnetoresistance in a Quantum Dot Coupled to Ferromagnetic Electrodes - Tang, Li-Wen; Mao, Wei-Guo (Frontiers in Physics, 2020)
We study quantum transport and tunneling magnetoresistance (TMR) through an interacting quantum dot (QD) attached to ferromagnetic electrodes in the Coulomb blockade regime. The QD is also side-coupled to a superconductor nanowire hosting Majarana bound states (MBSs). It is found that when the electrodes’ magnetic moments are arranged in antiparallel, the current’s intensity will be enhanced to be larger than that of the parallel configuration by the hybridization between the QD and the MBSs. This change in the current induces anomalous negative TMR unique to the existence of MBSs, providing an efficient detection way of the MBSs. The negative TMR is weakened by the overlap between the two bound states but obviously enhanced by the left-right asymmetry between the QD and the electrodes. We also find that the TMR value changes non-monotonously with the spin polarization of the electrodes. Our results may find real use in energy saving spintronic devices and quantum information processing.